Production of a Three-Dimensional Triangulated Irregular Network (3D TIN) for Al-Karkh University of Science, Baghdad- Iraq - Hamid, Huda M.; Al-Azawi, Fadia W. (Iraqi Journal of Science, 2021)
Many satellite systems take cover images like QuickBird for terrain so that these images scan be used to construct 3D models likes Triangulated Irregular Network (TIN), and Digital Elevation Model (DEM). This paper presents a production of 3D TIN for Al-Karkh University of Science in Baghdad - Iraq using QuickBird image data with pixel resolution of 0.6 m. The recent generations of high-resolution satellite imaging systems open a new era of digital mapping and earth observation. It provides not only multi-spectral and high-resolution data but also the capability for stereo mapping. The result of this study is a production of 3D satellite images of the university by merging 1 m DEM with satellite image for ROI using ArcGIS package Version 10.3.